Predictors of Mortality in Patients With Biopsy‐Proven Viral Myocarditis: 10‐Year Outcome Data. Issue 16 (18th August 2020) - Greulich, Simon; Seitz, Andreas; Müller, Karin A. L.; Grün, Stefan; Ong, Peter; Ebadi, Nawid; Kreisselmeier, Klaus Peter; Seizer, Peter; Bekeredjian, Raffi; Zwadlo, Carolin; Gräni, Christoph; Klingel, Karin; et al.
Abstract : Background: There is scarce data about the long‐term mortality as well as the prognostic value of cardiovascular magnetic resonance and late gadolinium enhancement (LGE) in patients with biopsy‐proven viral myocarditis. We sought to investigate: (1) mortality and (2) prognostic value of LGEcardiovascular magnetic resonance (location, pattern, extent, and distribution) in a >10‐year follow‐up in patients with biopsy‐proven myocarditis. Methods and Results: Two‐hundred three consecutive patients with biopsy‐proven viral myocarditis and cardiovascular magnetic resonance were enrolled; 183 patients were eligible for standardized follow‐up. The median follow‐up was 10.1 years. End points were all‐cause death, cardiac death, and sudden cardiac death (SCD). We found substantial long‐term mortality in patients with biopsy‐proven myocarditis (39.3% all cause, 27.3% cardiac, and 10.9% SCD); 101 patients (55.2%) demonstrated LGE. The presence of LGE was associated with a more than a doubled risk of death (hazard ratio [HR], 2.40; 95% CI], 1.30–4.43), escalating to a HR of 3.00 (95% CI, 1.41–6.42) for cardiac death, and a HR of 14.79 (95% CI, 1.95–112.00) for SCD; all P ≤0.009. Specifically, midwall, (antero‐) septal LGE, and extent of LGE were highly associated with death, all P <0.001. Septal LGE was the best independent predictor for SCD (HR, 4.59; 95% CI, 1.38–15.24; P =0.01). Conclusions: In patients with biopsy‐proven viral myocarditis, the presence of midwall LGE in the (antero‐) septal segments is associated with a higher rate of mortality (including SCD) compared with absent LGE or other LGE patterns, underlining the prognostic benefit of a distinct LGE analysis in these patients.